FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP SEDIKIT BANYAKNYA JAMA’AH SHOLAT SUBUH PADA MASJID/MUSHOLA DI KABUPATEN PONOROGO - Ahmad Muslich (AL-ASASIYYA: Journal Of Basic Education, 2017)
Abstraction, this research was done to answer the problem of researcher about the factor of the morphology of Ponorogo, this interesting aspect to be checked remembers quantitatively number of mosques/mushola in Ponorogo Regency from year is having year always experiences remarkable increase, even likely every RT/RW has mosque/mushola, but unhappily number of mosques the same of prayer at dawn This education explains about the factors of prayer at dawn and benefit prayer at dawn hour (clock, for behavior and believer Islam). This researcher has done with aproach of quatitative descriptive by using method interview, equipment and documentation Result of counselling researcher that management of mosque/musholla at dawn.